An investigation of polymorphisms in the 17q11.2-12 CC chemokine gene cluster for association with multiple sclerosis in Australians - Rubio Justin; Heard Robert; Bennetts Bruce; Booth David; Bugeja Matthew J; Stewart Graeme (BMC, 2006)
Abstract Background Multiple sclerosis (MS) is a disorder of the central nervous system (CNS) characterised by inflammation and neuronal degeneration. It is believed to result from the complex interaction of a number of genes, each with modest effect. Chemokines are vital to the migration of cells to sites of inflammation, including the CNS, and many are implicated in MS pathogenesis. Most of the CC chemokine genes are encoded in a cluster on chromosome 17q11.2-12, which has been identified in a number of genome wide screens as being potentially associated with MS. Methods We conducted a two-stage analysis to investigate the chemokine gene cluster for association with MS. After sequencing the chemokine genes in several DNA pools to identify common polymorphisms, 12 candidate single-nucleotide polymorphisms (SNPs) were genotyped in a cohort of Australian MS trio families. Results Marginally significant (uncorrected) transmission distortion was identified for four of the SNPs after stratification for several factors. We also identified marginally significant (uncorrected) transmission distortion for haplotypes encompassing the CCL2 and CCL11 genes, using two independent cohorts, which was consistent with recent reports from another group. Conclusion Our results implicate several chemokines as possibly being associated with MS susceptibility, and given that chemokines and their receptors are suitable targets for therapeutic agents, further investigation is warranted in this region.